Analisis Kebijakan Jalur Pejalan Kaki Dikaitkan dengan Peraturan Menteri Pekerjaan Umum Nomor 3 Tahun 2014 di Universitas Islam Negeri Sunan Gunung Djati Bandung - Rahayu Nur Halimah; Reyhan Aulia Dewi (UIN Sunan Gunung Djati Bandung, 2023)
Pedestrian paths are provided to be used as facilities for pedestrians safely and comfortably in accessing destinations. Sunan Gunung Djati State Islamic University with the main gate intersecting with the road as a place that is accessed by many students with walking facilities that are still misused. Therefore this study aims to analyze how these problems occur, the policies that have been implemented, as well as analyze the obstacles and supports for pedestrians. The research method used is descriptive research with a qualitative approach with data sources derived from primary and secondary data. The results of the study show that the pedestrian path to the west of the UIN Sunan Gunung Djati Bandung campus is still being misused by street vendors, while the east side of the campus which is under the authority of the campus has implemented protective facilities for pedestrians